Comparison of pharmacokinetic profiles of seven major bioactive components in normal and non-alcoholic fatty liver disease (NAFLD) rats after oral administration of Ling-Gui-Zhu-Gan decoction by UPLC-MS/MS - Nie, Wenlong; Yang, Yang; Li, Ling; Ding, Yue; Chen, Xingmi; Li, Ming; He, Ning; Ji, Guang; Zhang, Yong; Kang, Ping; Zhang, Tong (Frontiers in Pharmacology, 2023)
A sensitive and rapid ultra performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) method was hereby developed for the determination of seven components including glycyrrhizic acid, glycyrrhetic acid, dehydrotumulosic acid, isoliquiritin, liquiritin, atractylenolide III and cinnamic acid in the plasma of rats after oral administration of Ling-Gui-Zhu-Gan decoction (LGZGD). Besides, this very method was methodologically validated for specificity, linearity, inter-day and intra-day precision, accuracy, matrix effect, extraction recovery and stability. It was also successfully used for the first time to compare the pharmacokinetic characteristics of the seven components after oral administration of lingcodylic acid to normal rats and NAFLD rats. The results indicated significant differences in the pharmacokinetic characteristics of the normal rats and the NAFLD rats. To further reveal the different pharmacokinetic behaviours, the expression of enzymes and transporters in the liver of normal rats and NAFLD rats was detected using UPLC-MS/MS. In NAFLD rats, UDP-glucuronosyltransferase 1-1 (UGT1A1) and nine transporters were significantly inhibited, and a positive correlation was observed between them and the AUC of the major components. The present results indicate that the pharmacokinetic differences between the normal rats and the NAFLD rats might be attributed to the significantly lower expression levels of both the metabolic enzyme UGT1A1 and the nine transporter proteins compared with normal rats. Meanwhile, the UGT1A1 and nine transporter proteins might be used as potential biomarkers to assess the ameliorative effect of LGZGD on NAFLD, which could provide useful information to guide the clinical application of LGZGT.